Efektivitas Teknik Cognitive Behavioral Therapy (CBT) Untuk Meningkatkan Konsep Diri pada Siswa di UPTD SMP Negeri 1 Gunungsitoli Utara: Penelitian - Ningsih Rahman Zebua; Hosianna Rodearni Damanik; Famahato Lase; Justin Foera-Era Lase (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Self-concept is one of the key elements where individuals are able to understand their own identity from the influence of social interactions. However, in reality, students at UPTD SMP Negeri 1 Gunungsitoli Utara are still found to have a low self-concept. So that with this, students experience obstacles both in recognizing themselves, disrupting their learning process, so that students tend to stay away from social interactions in their environment. The purpose of this study was to improve students' self-concept through individual counseling services with Cognitive Behavioral Therapy (CBT) techniques. This type of research is quantitative research with an experimental approach. Based on the results of the study, it was found that the posttest value in the experimental group was 82.93 higher than the posttest value in the control group 56.93. The value of the two groups indicates that in the experimental group the service is more effective in improving students' self-concept. This can be strengthened based on the results of the N-gain test in the experimental class, which is 67.6701 / 68% in the moderately effective category (56-75%). So it can be concluded that the provision of individual counseling services with CBT techniques is declared quite effective.